Influence of soft tissue in the assessment of the primary fixation of acetabular cup implants using impact analyses. (June 2018) - Bosc, Romain; Tijou, Antoine; Rosi, Giuseppe; Nguyen, Vu-Hieu; Meningaud, Jean-Paul; Hernigou, Philippe; Flouzat-Lachaniette, Charles-Henri; Haiat, Guillaume
Abstract: Background: The acetabular cup (AC) implant primary stability is an important determinant for the success of cementless hip surgery but it remains difficult to assess the AC implant fixation in the clinic. A method based on the analysis of the impact produced by an instrumented hammer on the ancillary has been developed by our group (Michel et al., 2016a). However, the soft tissue thickness present around the acetabulum may affect the impact response, which may hamper the robustness of the method. The aim of this study is to evaluate the influence of the soft tissue thickness (STT) on the acetabular cup implant primary fixation evaluation using impact analyses. Methods: To do so, different AC implants were inserted in five bovine bone samples. For each sample, different stability conditions were obtained by changing the cavity diameter. For each configuration, the AC implant was impacted 25 times with 10 and 30 mm of soft tissues positioned underneath the sample. The averaged indicator I m was determined based on the amplitude of the signal for each configuration and each STT and the pull-out force was measured. Findings: The results show that the resonance frequency of the system increases when the value of the soft tissue thickness decreases. Moreover, an ANOVA analysis shows that there was no significant effect of the value of soft tissue thickness on the values of the indicator I m ( F = 2.33; p -value = 0.13). Interpretation: This study shows that soft tissue thickness does not appear to alter the prediction of the acetabular cup implant primary fixation obtained using the impact analysis approach, opening the path towards future clinical trials. Highlights: No effect of the tissue thickness is observed on the indicator of implant stability The resonance frequency decreases when soft tissue thickness increases The indicator derived from impacts measurements can be used to assess the acetabular cup stability in vitro